Optimization of Sweet Sorghum (Sorghum Bicolor L. Moench) Clarifying Process Using a Centrifugation: Optimasi Proses Penjernihan Nira Sorgum Manis (Sorghum Bicolor L. Moench) Menggunakan Sentrifugasi - Istianah, Nur; Fatmala, Yayank Ulfa; Ali, Dego Yusa; Putri, Widya Dwi Rukmi (Jurnal Pangan dan Agroindustri, 2025)
Abstract Sweet sorghum juice is currently widely used as raw material for bioethanol and can potentially be converted into liquid sugar. However, impurity particles from the extraction process are still an issue in fermentation and evaporation. This study aims to determine the optimal conditions for the sorghum juice clarification process through the centrifugation process by analyzing the effect of rotation speed (300-700 RPM) and centrifugation time (45-75 minutes) on turbidity and total dissolved solids (TSS) parameters using the Response Surface Methodology (RSM) method. The results showed that rotation speed and centrifugation time significantly affected turbidity and TSS values. The optimum conditions were obtained at a rotation speed of 500 RPM for 53.49 minutes with a turbidity value of 2.02 NTU and TPT of 17.93 °Brix. These results are expected to provide information on the best conditions for the sorghum juice clarification process using centrifugation. Abstrak Nira sorgum manis saat ini banyak digunakan untuk bahan baku bioetanol dan berpotensi untuk diolah menjadi gula cair. Namun, partikel pengotor dari proses ekstraksi masih menjadi permasalahan baik pada proses fermentasi maupun evaporasi. Penelitian ini bertujuan untuk menentukan kondisi optimal proses penjernihan nira sorgum melalui proses sentrifugasi dengan menganalisis pengaruh kecepatan putar (300-700 RPM) dan lama sentrifugasi (45-75 menit) pada parameter turbiditas dan total soluble solid (TSS) menggunakan metode Response Surface Methodology (RSM). Hasil penelitian menunjukkan bahwa kecepatan putar dan lama sentrifugasi memiliki pengaruh signifikan pada nilai turbiditas dan TSS. Adapun kondisi optimum didapatkan pada kecepatan putar 500 RPM selama 53,49 menit dengan nilai turbiditas 2,02 NTU dan TPT 17,93 0Brix. Hasil ini diharapkan mampu memberikan informasi kondisi terbaik pada proses penjernihan nira sorgum menggunakan sentrifugasi.